Pengaruh Variabel Sosial Demografi terhadap Keputusan Penduduk Lanjut Usia Memilih Bekerja di Kecamatan Kediri - Utami, Ni Putu Dewi; Rustariyuni, Surya Dewi (Jurnal Ekonomi Kuantitatif Terapan, 2017)
The phenomenon of population aged 60 years and older who can be categorized as elderly people still working are found in Bali. Improving the quality of health has an impact on increasing life expectancy may indirectly increase the number of elderly people who are still working. This study aims to determine the impact of socio-demographic variables on the decision of elderly people choose to work. The data collection was conducted using interviews and questionnaires in the district of Kediri Tabanan. The sample data was obtained by proportionate random sampling with a sample of 191 respondents. This study uses a logit model analysis.The research result shows that the decisions of elderly people choose to work in the district of Kediri, Tabanan regency is affected by marital status, old age benefits, age, sex, and health conditions. Education, dependency and status in the family did not significantly impact the decisions of elderly people choose to work in the district of Kediri, Tabanan regency.
Keywords: status perkawinan; tunjangan hari tua; usia; jenis kelamin; pendidikan